Nurses’ Role in Home Care’s Older Adult with Frailty - Klinpudtan, Nonglak; Tongma, Sichon; Klinchet, Nuntikan; Srithumsuk, Werayuth (Journal of The Royal Thai Army Nurses, 2022)
Frailty is a common clinical syndrome and associated with declining in older adult that affect the quality of life of older adult and caregivers. Frailty will become more severe if they have other chronic diseases. Therefore, nurses play an important role in prevention, care, and rehabilitation of frailty to improve older adult’s quality of life by home care services. A frailty’s diagnosis consisted of at least three abnormal components out of five components were low grip strength, slow walking speed, low physical activity, unintentional weight loss, and exhaustion. The risk factors of frailty are related to genetic and environmental factors. Recently, the most common instrument for screening frailty is Freid’s phenotype instrument. There are divided the severity of frailty into 2 phases that were pre-frailty and frailty phases. Nurses are the facilitators and supporters of the patients and their families to follow the treatment protocol both pre-frailty and frailty phases. This implementation helps for prevention, caring, and rehabilitation to improve quality of life in older adult.